Model for calculation spectral density electromyographic signal during electrostimulation - Prasol, I.; Yeroshenko, O. (My University, 2022)
In the course of the study, the structure of the spectrum of the electromyographic signal was obtained, which is represented as a sum of periodically following pulses shifted relative to each other in time. An analytical relationship has been established between the statistical properties of a random phase difference and the type of signal power spectrum. The obtained theoretical relations allow us to calculate the spectral density of the electromyographic signal depending on the number of motor units and various phase shifts between them
Keywords: skeletal muscle; motor unit; electrical signal; mathematical modeling; spectral density; electromyographic signal; electrical stimulation